Progresifitas Regulasi Keuangan Syariah Di Indonesia - Ulum, Fahrur (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2017)
Abstract: This paper discusses about the progressive regulation of Islamic finance in Indonesia and its relation with the government's political will in shari’ah financial institutions. The progress of shari’ah financial regulation in Indonesia is good enough to solve various demands of operational optimization of shari’ah financial institutions in Indonesia. It shows that shari’ah financial regulation is massive and experiencing good progressive to answer operational problems of shari’ah financial institutions. The situation is also reinforced by the massive of the fatwa of the National Shari’ah Council (DSN). Various development programs of Islamic financial institutions conducted by the government through Bank Indonesia, BAPEPPAM, Financial Services Authority (OJK), and DSN show the existence of political will of the government to shari’ah financial institutions. To give a certain regulation in order to optimize the operational of shari’ah financial institutions, the government has massively issued various regulations. The progressiveness of shari’ah financial regulations prove that the political will of the government is seen in the effort of developing syari’ah financial institutions. Abstrak: Tulisan ini membahas tentang progresifitas regulasi keuangan syariah di Indonesia dan kaitannya dengan political will pemerintah pada lembaga keuangan syariah. Progres regulasi keuangan syariah di Indonesia cukup bagus untuk menyelesaikan berbagai tuntutan optimalisasi operasional lembaga keuangan syariah di Indonesia. Hal itu menunjukkan bahwa regulasi keuangan syariah cukup masif dan mengalami progresifitas yang baik untuk menjawab persoalan-persoalan operasional lembaga keuangan syariah. Keadaan tersebut diperkuat dengan progres fatwa Dewan Syariah nasional (DSN) yang cukup masif pula. Berbagai program pengembangan lembaga keuangan syariah yang dilakukan oleh pemerintah melalui Bank Indonesia, BAPEPPAM, Otoritas Jasa Keuangan (OJK), dan DSN menunjukkan adanya political will pemerintah terhadap lembaga keuangan syariah. Untuk menjawab kepastian regulasi demi optimalisasi operasional lembaga keuangan syariah, pemerintah secara masif mengeluarkan berbagai regulasi keuangan syariah. Progresifitas regulasi keuangan syariah menjadi bukti bahwa political will pemerintah tampak dalam upaya pengembangan lembaga keuangan syariah.